Türkiye’de yaygın tilavet geleneği ve fonetik tahlili - Mısırlı, Fatma Yasemin (My University, 2017)
İslam ülkeleri arasında Türkiye olarak kendimize özgün bir tilâvet geleneğine sahibiz. Tilâvetimizin karakteristik özellikleri ülkemiz dışındaki islam dünyasıyla farklılık arzetmekte. Bu farklılıklar Kur’ân doğrularına zarar vermeyen bize özgü hususiyetler midir? Yoksa bu durum bir hatalı okuma boyutuna mı gelmiştir? Meseleye, okuyuş tarzı, makam ve uslüb yönü gözardı edilerek, sadece mahrec, sıfat, tecvit uygulamaları ve bunlara müteallik bir kaç husus çerçevesinde yaklaşılmıştır. Kur’ân tilâveti bize nasıl ulaşmıştır? Rasulullah’dan (sav) bu yana bizlere doğru seslerin ulaşabilmesi için gözetilen kriterler nelerdir? Bu kriterlerden biri olan rivâyet boyutu tarihi seyriyle araştırılmış ve ülkemizdeki kıraatin rivâyet yönüyle nereye dayandığı ortaya konulmaya çalışılmıştır. İkinci kriter olan dirâyet boyutu tarihi seyriyle ortaya konmuş ve ülkemizdeki tilâvetin dirâyet temelleri tesbit edilmeye çalışılmıştır. Ele geçirilen ip uçları ve bulgular tilâveti etkileyen her husus için değerlendirilerek, doğruların ve yanlışların tesbiti yoluna gidilmiştir.Bu doğrular ve yanlışlar sonrasında yapılması gerekenin ne olduğu, karakteristik özelliklerimizi terketmeden, hataya da düşmeden nasıl bir yol izleyebileceğimiz ve bundan sonrası için bu konuda ne gibi çalışmalar yapılabileceğimiz yine bu çalışmanın değindiği konular arasındadır.

Turkey has its own Qur’an recitation tradition that is distinguished from all other Muslim countries around the World. The characteristic attributes of this particular recitation style presents clear and distinct differences in the recitation style among the Muslim World. This study delves into these differences that are particular to Qur’an recitation tradition in Turkey to find out whether they can be classified as idiosyncratic differences that does not alter the meaning of Qur’an. It further yearns to analyse if these idiosyncracies constitute mistakes in Qur’an recitation. The approach that is adopted in this study focuses on the phonological aspects of recitation such as the points and manners of articulation and the connected speech processes or phonological rules of Arabic sounds, disregarding any differences due to melodious recitation styles.How did the recitation of Qur’an reach us? What are the criteria to ensure the precision and accuracy of the sounds from Rasulullah SAW till today? Riwayah, authentic chain of narrations from the Prophet SAW, is one of the criterion in the process of determining such accuracy. Qur’an teaching and recitation in Turkey have been thoroghly investigated through its historical course to verify whether or not those practices have been based on authentic narrations or riwayah. The same meticulous approach was also applied for he second criterion, dirayah, sagacity of collective accumulated wisdom through the couse of history, thus revealing the foundations of the idiosyncracies in the Turkish recitation of Qur’an. The outcome and conclusions obtained as a result of this study were evaluated in reference to phonological aspects of recitation as well as the connected speech processes or phonological rules of Arabic sounds, hence designating the correct and mistaken practices. After the establishment of the correct and mistaken practices, the study further explores what course of action should be taken in teaching the authentic way of Qur’an recitation without abandoning our characteristic attributes while at the same time avoiding to fall into error. Suggestions for new methodologies that will unite Turkey with the rest of the Muslim World based on authentic narrations are also included in the study.
Keywords: Characteristic Attiributes; Dirayah; Dirayet; İslam dini; Karakteristik Özellikler Riwayah; Kur'an; Kur’an; Kuran okuma; Rivayet; Tilavet